Influência do treinamento da musculatura inspiratória nas alterações hemodinâmicas, pulmonares e autonômicas em pacientes com DPOC - FRANÇA, Ana Lídia de Carvalho Cutrim (2018)
Introduction: Chronic Obstructive Pulmonary Disease (COPD) is one of the leading causes of death worldwide. Non-pharmacological interventions have successfully increased quality of life in these patients. Among these interventions, there is inspiratory muscle training, and no study has investigated its effect on autonomic modulation in patients with COPD. Methods: Two groups (n=22) of COPD patients joined the study. The patients were randomly assigned to the inspiratory muscle training group (IMT; n=11) and to a control group (CG; n=11). Spirometry, heart rate variability and the 6-minute walking test (6MWT) were made before and after a protocol of 12 weeks of IMT at 30% of the maximal inspiratory pressure (MIP) and, on the control group. Results: Heart rate variability increased in the time domain, as expressed by SDNN, RMSSD, Total variability, SD1, SD2 and HF (ms2) in the IMT group versus control group. Also, the IMT increased the 6MWT distance and the peak oxygen consumption. No changes in the spirometry volumes were found in both groups. Conclusion: 12 weeks of IMT at 30% of the MIP increased heart rate variability and exercise tolerance in COPD patients.